Distributed system of low-consumption sensors to monitor environmental variables in indoor spaces - Palacios, Oliver; Plaza Vargas, Angel Marcel; Lino Castillo, Katty Nancy (EASI: Engineering and Applied Sciences in Industry, 2022)
Currently, the analysis of air quality and environmental conditions in indoor environments have been an important subject of study, because people spend most of the day in closed places, such as buildings, houses, classrooms, offices, etc. This article describes the development of a prototype of a distributed network of environmental sensors, which are responsible for measuring the environmental variables of humidity and temperature, with efficient sensors, low cost and low energy consumption. This system allows monitoring three different points within a different environmental setting, located in strategic places, thus obtaining a different sample. The prototypes capture the measurements of the environmental variables and register them in a database contained in a web server to later be presented to the end user. These measurements are made and displayed in real time.